Investigating the mechanical properties of cortical bone under dynamic torsional loading - Jianyin Lei; Zhiyang Li; Hengru Su; Shiqiang Li; Zhifang Liu (Theoretical and Applied Mechanics Letters)
Bone is a multi-phase, non-homogeneous material that exhibits strain rate sensitivity, and it may fail under compression, tension, torsion, or a combination of these loading. The mechanical properties of cortical bone with strain rate effect under compression and tension have been obtained through the application of the split Hopkinson pressure/tension bar technique, but no such studies have been reported for determining the strain rate behavior properties of bony materials under torsion. In this study, the shear stress-strain curves with the rate-dependent cortical bone subjected to dynamic torsional loading were first obtained using a torsional split Hopkinson bar system. Based on the experiments, an improved mathematical model consisting of elastic, viscoelastic, and viscoplastic components was used to identify the material parameters of the cortical bone. Detailed material properties are derived through constitutive relations. The results may assist researchers in developing more accurate models of cortical bone behavior under different load conditions.